Mecanismos eletroquímicos nos processos de descarga do sistema PbO2/H2SO4 - Freitas, Heverson Renan de (Universidade Federal de São Carlos, 2017)
The goal of this work was to seek a mechanistic and morphological understanding of the discharge process of lead-acid batteries’ positive plates, which exhibits a complex porous structure. Due to this fact, nonporous electrodes, ideally porous electrodes and positive plates were investigated. Studies on the discharge process of nonporous electrodes facilitated the reactional processes understanding from a mechanistic and morphological point of view. It was shown the existence of two steps during the discharge process. The first step is easily invertible and follows a solid state reaction mechanism, in which is possible to calculate the ionic resistivity evolution during the voltametric transient. The discharge product of the first step seems to be a PbOn1 electronic conductor (due to its stoichiometry) and, from the fact that it is a very thin film attached to the surface, this product was not observable by SEM measurements. On the other hand, the second step is not easily invertible and occurs at slower rates. During the second step, there is a stoichiometric change on the discharge product of the first step, giving rise to a PbOn2 (unstable and electronic insulator) that reacts with H2SO4 on the solution and forms lead basic sulfates. By the end of the second step, the discharge products give rise to structures observable by SEM measurements, which result from a dissolution/precipitation mechanism (that may occur due to longer processes times). The final stationary potential for discharge process of the PbO2/H2SO4 system was determined. Studies on ideally porous electrodes made it clear the existence of a zonal character of the discharge reactions. Studies on positive plates allowed the understanding of how complex the kinetic processes are on porous electrodes when compared to nonporous systems. Due to the structural complexity and the reactional zonal character, the transformations are much slower (time order of months). Besides that, the equilibrium O2/H2O must be taken into account to understand the results on positive plates, due to O2 bubbles trapped inside the pores during previous charge processes. These interpretations were made possible by Open Circuit Potential measurements assisted by concepts of Mixed Potential and Dynamical Systems Theories, specially the concept of attractor. This methodology allowed a new approach to electrochemical processes that implies multiple electrodes.
Electrochemichal mechanisms in the discharge processes of PbO2/H2SO4 system
Keywords: Baterias de chumbo-ácido; Dióxido de chumbo; Filmes de passivação; Reação de estado sólido; Placa positiva; Lead-acid battery; Lead dioxide; Passivation films; Solid state reactions; Positive plate; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA::CINETICA QUIMICA E CATALISE; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA::ELETROQUIMICA; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA